Microsatellite instability status determined by next‐generation sequencing and compared with PD‐L1 and tumor mutational burden in 11, 348 patients. (13th February 2018) - Vanderwalde, Ari; Spetzler, David; Xiao, Nianqing; Gatalica, Zoran; Marshall, John
Abstract: Microsatellite instability (MSI) testing identifies patients who may benefit from immune checkpoint inhibitors. We developed an MSI assay that uses data from a commercially available next‐generation sequencing (NGS) panel to determine MSI status. The assay is applicable across cancer types and does not require matched samples from normal tissue. Here, we describe the MSI‐NGS method and explore the relationship of MSI with tumor mutational burden (TMB) and PD‐L1. MSI examined by PCR fragment analysis and NGS was compared for 2189 matched cases. Mismatch repair status by immunohistochemistry was compared to MSI‐NGS for 1986 matched cases. TMB was examined by NGS, and PD‐L1 was determined by immunohistochemistry. Among 2189 matched cases that spanned 26 cancer types, MSI‐NGS, as compared to MSI by PCR fragment analysis, had sensitivity of 95.8% (95% confidence interval [CI] 92.24, 98.08), specificity of 99.4% (95% CI 98.94, 99.69), positive predictive value of 94.5% (95% CI 90.62, 97.14), and negative predictive value of 99.2% (95% CI, 98.75, 99.57). High MSI (MSI‐H) status was identified in 23 of 26 cancer types. Among 11, 348 cases examined (including the 2189 matched cases), the overall rates of MSI‐H, TMB‐high, and PD‐L1 positivity were 3.0%, 7.7%, and 25.4%, respectively. Thirty percent of MSI‐H cases were TMB‐low, and only 26% of MSI‐H cases were PD‐L1 positive. The overlap between TMB, MSI, and PD‐L1 differed among cancer types. Only 0.6% of the cases were positive for all three markers. MSI‐H status can be determined by NGS across cancer types. MSI‐H offers distinct data for treatment decisions regarding immune checkpoint inhibitors, in addition to the data available from TMB and PD‐L1. Abstract : MSI‐H status can be determined by NGS across cancer types without requiring a matched tissue sample. MSI‐H offers distinct data for treatment decisions regarding immune checkpoint inhibitors, in addition to the data available from TMB and PD‐L1.